Analisis Yuridis Pasal 93 Ayat (1) Undang-Undang Nomor 28 Tahun 2009 tentang Pajak Daerah dan Retribusi Daerah - Hidayat, Ophie Rosaria (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to analyze the party that authorized to impose sanctions on officials making land deeds related to violations of Article 93 paragraph (1) of Law Number 28 of 2009 and the juridical implications of Article 93 paragraph (1) of Law Number 28 of 2009 regarding administrative fines which were not paid. The type of research in this study was normative juridical with a statutory approach and a case approach. The results of this study indicated that Article 93 paragraph (1) of Law Number 28 of 2009 concerning Regional Taxes and Regional Levies did not regulate officials or agencies that were given the authority to give administrative sanctions to land certificate makers who committed violations. The occurrence of a legal vacuum became a problem so that the regulation cannot be implemented effectively. The juridical implications of Article 93 paragraph (1) of Law Number 28 of 2009 regarding administrative fines were not paid, namely that the prosecutor’s office took part in the problem due to the absence of follow-up actions related to the fines for land deed officials even though they have been given a warning letter and have not fulfilled their obligations to pay administrative fines.